Superparamagnetic iron oxide nanoparticle 'theranostics'' for multimodality tumor imaging, gene delivery, targeted drug and prodrug delivery. Issue 1 (January 2010) - Yu, Yanke; Sun, Duxin
The superparamagnetic iron oxide nanoparticle (SPIO) 'theranostics'', which contain imaging probes for tumor diagnosis and therapeutic compounds for therapy in a single nanoparticle, might provide significant benefits compared with exiting tumor imaging and therapeutic strategies. In this review, we summarize the progress of SPIO 'theranostics'' that integrate tumor targeting, multimodality imaging, and gene delivery or targeted drug and prodrug delivery. This review describes various methods of SPIO synthesis, surface coating and characterization. Different tumor-targeting strategies, such as antibody fragments, nucleotides and receptor ligands, are discussed to improve SPIO delivery for multimodality imaging. We also examine the utility of SPIOs for gene delivery, siRNA delivery and imaging. Several methods for drug encapsulation and conjugation onto SPIOs are compared for targeted drug delivery, site-specific release and imaging-guided drug delivery. Finally, we also review the pharmacokinetics (including biodistribution) of SPIOs based on their characteristics.